A NEW SPECIES OF OPHIORRHIZA (RUBIACEAE) FROM GREAT NICOBAR ISLAND, INDIA - N. P. BALAKRISHNAN (Reinwardtia, 1980)
Ophiorrhiza nicobarica Balakr.is described and illustrated and compared with Ophiorrhiza trichocarpos Bl.